Kemandirian Badan Usaha Milik Negara: Persinggungan Antara Hukum Privat Dan Hukum Publik - Yoyo Arifardhani (Otentik's : Jurnal Hukum Kenotariatan, 2019)
The legal status of state-owned enterprises (BUMN) cannot be separated from the state finance conception. In addition to the dualism of legislation that applies with regard to state finances, there are also intersections between private law and public law. The use of a civil action mechanism, internal supervision and the application of the private law domain to state-owned enterprises based on the Limited Liability Company Law on indications of mismanagement of state-owned enterprises, so that the Directors of BUMN may be criminally responsible for the losses of state-owned enterprises. The judicial review of the Supreme Audit Board (BPK) law is based on the view that the state's financial scope is only the state budget, while the state's assets outside the state budget, such as the assets separated from state-owned enterprises are not state finances. The issue of the constitutionality of the BPK's authority in examining state financial management carried out on state-owned enterprises is deemed inconsistent with the objectives of BUMN which are expected to be independent, prioritizing the principles of good corporate governance, even though the Constitutional Court in Decision Number 48 and Number 62/PUU-XI/2013 rejected the application and the BPK still has the authority to supervise state-owned enterprises.